International Monetary Fund Annual Report 1959. (Annual Report of the Executive Board; Annual Report of the Executive Board ;, 1959)
This paper reviews key findings of the IMF's Annual Report for the fiscal year ended April 30, 1959. The report highlights that the year that ended on April 30, 1959, stands out not only because of the marked changes that occurred in general business activity and in the international flow of funds, but also because important steps were taken to consolidate the monetary improvements achieved since the war and to strengthen the financial structure of the world economy.